Legal Assistance for the Community in Cases of Sexual Violence - Salim; Leni Indrayani; Junaidi Lubis (Outline Journal of Community Development, 2023)
This activity uses a qualitative approach with a socio-legal research method to analyze the effectiveness of legal assistance for victims of sexual violence in Indonesia. Data were collected through literature studies, in-depth interviews, and participant observation. The results of the study indicate that comprehensive legal assistance, including psychological services, can improve access to justice for victims. However, there are still obstacles in coordination between legal aid institutions, law enforcement officers, and civil society organizations. This study recommends increasing training for legal assistants, educating the community, and strengthening regulations so that the assistance system is more pro-victim. In addition, the use of technology in legal aid services can be a solution to expand the reach of assistance. With these steps, it is hoped that victims of sexual violence can obtain better legal protection and a justice system that is more responsive to their needs.